2020
DOI: 10.1093/ptep/ptaa056
|View full text |Cite
|
Sign up to set email alerts
|

Application of independent component analysis to the iKAGRA data

Abstract: We apply independent component analysis (ICA) to real data from a gravitational wave detector for the first time. Specifically, we use the iKAGRA data taken in April 2016, and calculate the correlations between the gravitational wave strain channel and 35 physical environmental channels. Using a couple of seismic channels which are found to be strongly correlated with the strain, we perform ICA. Injecting a sinusoidal continuous signal in the strain channel, we find that ICA recovers correct parameters with en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…( 9) coincides with the Wiener filtering for two channels and it turns out to be a optimal subtraction method for the coupling (6) in the context of ICA. In our previous work [23], we showed that the above discussion is generalized to arbitrary number of witness channels x i (t) (i = 1, ..., n) and confirmed that the performance of this method corresponding to the Wiener filtering [24] was better than FastICA in subtracting seismic noise from iKAGRA data. Based on this result, we extend the model of mixing matrix (6) by incorporating the effect of time delay, or the frequency dependence in the following.…”
Section: Conceptual Introduction Of Ica and Its Application To Noise ...supporting
confidence: 64%
See 3 more Smart Citations
“…( 9) coincides with the Wiener filtering for two channels and it turns out to be a optimal subtraction method for the coupling (6) in the context of ICA. In our previous work [23], we showed that the above discussion is generalized to arbitrary number of witness channels x i (t) (i = 1, ..., n) and confirmed that the performance of this method corresponding to the Wiener filtering [24] was better than FastICA in subtracting seismic noise from iKAGRA data. Based on this result, we extend the model of mixing matrix (6) by incorporating the effect of time delay, or the frequency dependence in the following.…”
Section: Conceptual Introduction Of Ica and Its Application To Noise ...supporting
confidence: 64%
“…While the principle of ICA based on the statistical independence is so general that it is applicable to the nonlinearly coupled system [25], it makes the calculation more transparent compared to the machine learning. In the previous study [23], we demonstrated that the seismic noise can be partially subtracted by the simplest model of ICA. Note that the model assuming instantaneous linear mixing, was implemented in two different ways and the optimal case turned out to be the time domain Wiener filtering [24,25].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The acoustic noise limited the O3GK sensitivity in some frequencies between 100 Hz and 400 Hz. Therefore, the following approaches are planned to reduce them in the next observation: (1) Introduction of soundproofing material at the experimental site to reduce the acoustic field, (2) Mitigation of scattered light propagation using new optical baffles and beam dumps inside and outside the vacuum enclosure in addition to the currently 21/37 installed ones [7], (3) Acoustic contamination in the DARM signal subtracted by independent component analysis performed in the iKAGRA study [12].…”
Section: Noise Contribution Between 100 Hz and 400 Hzmentioning
confidence: 99%